(untitled) (Al-Academy, 2022)
The theatrical performance has an aesthetic, artistic, technical and intellectual vision presented by the theatrical director according to the dualities of theatrical form and content, which depend on the uniformity and interconnection of theatrical elements, as the vision is integrated through the harmony and fusion of these elements and the flow of their coordination with an aesthetic system within the framework of the aesthetic space of the theatrical performance, and when the heritage is presented in the performance, as there will certainly be different readings of that heritage and moving away from the iconization of the event and highlighting it in a manner that is in line with the spirit of the age. the (researcher) tries, through her research headlined (directorial vision and sociological adaptation of heritage in theatrical performance), to grasp the hypothesis of heritage at the levels of time, place, event, topic and mechanism of action. And the director’s adaptation of heritage and his aesthetic vision, sociologically.The research is formed through two axes, the first is the research in the sociology of theater throughout history and the discussion of the sciences that presented those hypotheses and the philosophers who contributed to finding the determinants and features of sociology, theatrically, and through living experiences that presented the directorial adaptations to it through different societies and the mechanism of the director’s work on those adaptations.The (researcher) also presented another topic that discussed the references of directorial visions and their sociological adaptation of heritage in theatrical performance through a group of performances that contributed to presenting directorial visions of heritage in their various theatrical experiences, and she (the researcher) also referred to some indicators that will contribute to analyzing the research sample descriptively because it represents a criterion in the work of (the researcher), to come up with a set of results through which it is possible to refer to some conclusions to reach satisfactory answers to the research problem, which is the question of what are the epistemological references of the directorial vision, sociologically, in the adaptation of heritage in theatrical performance